The Fermi-LAT gamma-ray excess at the Galactic Center in the singlet-doublet fermion dark matter model (2016)
ABSTRACT: The singlet-doublet fermion dark matter model (SDFDM) provides a good DM candidate as well as the possibility of generating neutrino masses radiatively. The search and identification of DM requires the combined effort of both indirect and direct DM detection experiments in addition to the LHC. Remarkably, an excess of GeV gamma rays from the Galactic Center (GCE) has been measured with the Fermi Large Area Telescope (LAT) which appears to be robust with respect to changes in the diffuse galactic background modeling. Although several astrophysical explanations have been proposed, DM remains a simple and well motivated alternative. In this work, we examine the sensitivities of dark matter searches in the SDFDM scenario using Fermi-LAT, CTA, IceCube/DeepCore, LUX, PICO and LHC with an emphasis on exploring the regions of the parameter space that can account for the GCE. We find that DM particles present in this model with masses close to ∼ 99 GeV and ∼(173–190) GeV annihilating predominantly into the W+W− channel and tt ̄ channel respectively, provide an acceptable fit to the GCE while being consistent with different current experimental bounds. We also find that much of the obtained parameter space can be ruled out by future direct search experiments like LZ and XENON-1T, in case of null results by these detectors. Interestingly, we show that the most recent data by LUX is starting to probe the best fit region in the SDFDM model.